2017
DOI: 10.12998/wjcc.v5.i8.324
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of sepsis: What is the antibiotic choice in bacteremia due to carbapenem resistantEnterobacteriaceae?

Abstract: Sepsis is one of the major challenges of today. Although gram-positive bacteria related infections are more prevalent in hospital setting, the highest mortality rate is associated with gram-negative microorganisms especially Enterobacteriaceae. Enterobacteriaceae, including Escherichia coli, Klebsiella spp., Proteus spp., Enterobacter spp. and Serratia spp. Resistance to β-lactams in Enterobacteriaceae is primarily attributed to the production of B-lactamase enzymes with subsequent antibiotic hydrolysis and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
1
25
0
2
Order By: Relevance
“…In addition to reducing the development of resistance in the clinic and the environment (30), accumulating evidence shows that combination therapy boosts survival compared to monotherapy, especially in patients with bacteremia and patients who are critically ill (31)(32)(33). Similarly, we found that combination therapy seems to be more effective than monotherapy, although monotherapy is not any more effective than therapy with inactive drugs, as previously reported by Tzouvelekis et al (34).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to reducing the development of resistance in the clinic and the environment (30), accumulating evidence shows that combination therapy boosts survival compared to monotherapy, especially in patients with bacteremia and patients who are critically ill (31)(32)(33). Similarly, we found that combination therapy seems to be more effective than monotherapy, although monotherapy is not any more effective than therapy with inactive drugs, as previously reported by Tzouvelekis et al (34).…”
Section: Discussionsupporting
confidence: 86%
“…mortality in the tigecycline monotherapy group. Although an optimal combination therapy against CRE has not yet been established (30), combination therapy that includes meropenem was associated with significantly better survival. Indeed, regimens based on two carbapenems were previously recommended for CRKP infection when meropenem MICs were Յ8 mg/liter (11,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, genes including imiS 54 , NDM-9 55 , or THIN-B 56 (which may encode carbapenemase activity against meropenem) indicates meropenem treatment alone may not be sufficient to clear this K. pneumoniae infection, and a combination therapy e.g. meropenem with ertapenem may be required 57 . Overall, information at only 10 hours, which would correlate with presentation of first NEC symptoms, is clinically very relevant and potentially provides important information on the pathogen involved and associated AMR profiles that may guide antibiotic treatment choices.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also studies showing that early combination therapy is associated with lower mortality in patients with septic shock [83] . Combination therapy is preferred when treating sepsis patients for whom carbapenem-resistant Enterobacteriaceae (CRE) is considered the causative agent, due to its synergistic effect and to prevent the development of resistance [84] . Combination therapy with aminoglycoside has been associated with higher survival rates in cases of sepsis and septic shock due to Gram-negative bacteria with high risk of MDR, such as Pseudomonas spp.…”
Section: Antimicrobial Therapymentioning
confidence: 99%